Detrimental effects of early rural life on blood pressure among urban male migrants in Wrocław, Poland - Kozieł, Sławomir; Lipowicz, Anna; Ulijaszek, Stanley J. (Anthropological Review, 2012)
The purpose of the study was to compare the blood pressure of rural–to–urban migrants and the sedentary population (non–migratory) of the city of Wrocław, Poland. Additionally, the effect of time spent in the rural area on blood pressure was also assessed. The study sample consisted of 2753 males aged 25–75 years, following a medical examination, underwent an interview and anthropometric measurements between 1989–90. Based on the place of origin all males were divided into rural–to–urban migrant inhabitants of Wrocław (N=1222) and sedentary inhabitants of Wrocław (N=921). The percentage of time spent in the rural area [(time spent in rural area/age)*100] was then calculated and was used in analysis. In each age category, the rural–urban migrants were found to be shorter in height. Age, BMI, level of education and time of migration had a significant effect on both the systolic and diastolic blood pressure irrespective of the level of education. It was demonstrated that the time of migration, allowing for age, body size and education level, significantly correlated with blood pressure. The later in time, the males migrated from rural to urban areas, the higher their blood pressure. It was hypothesized that unhealthy behavior could still have continued in a new urban environment, resulting in migrant – sedentary differences in health parameters.